A closed-form general solution for the distance of point-to-parabola in two dimensions. (27th June 2022) - Chou, Chang-Chien
This paper resolves a closed-form general solution for the distance from a point to a parabola in a two-dimensional plane. This is the quickest way to answer the question with exact value. Although the method for resolving the general solution is somewhat fundamental, so far there is no efficient way provided in the literature than we do in this work. The closed-form general solution takes O(1) instant time answering the question and thus should be archived. Versatile applications need to compute the distance among parabolas in 2D. Practitioners in all fields may access the source code in the appendix for rapid conducting to their applications.